(untitled) (Patan Prospective Journal, 2024)
This article explores the complications of Nepali-English legal translation by examining linguistic and extra linguistic complications between Nepali and English languages and proposes a solution. Law offers rights and binds people with duties within a jurisdiction, and translating law from one language to another language brings complications for equal communication. The knowledge of comparative law and the incompetence of the source and the target language culture interfere with natural communication. Even a minor mistake in translation brings major disputes and conflicts. As the theoretical framework, this research uses equivalence and cultural theories of legal translation. It collects primary and secondary data from freelance and institutional translations applying juritraductological methods used in legal translation. The significance of the study is to professionals, novice translators, and university student’s curious about Nepali-English legal translation. This research finds that translating law or legal documents from one language to another language brings linguistic and extra linguistic complications, but a translator can resolve the musing the proposed solutions. It concludes that exploring the complications of Nepali-English legal translation with solutions enhances the quality of Nepali legal translation.